Single‐center experience with partial support device in destination therapy for end‐stage heart failure. Issue 10 (12th July 2020) - Barbone, Alessandro; Pagliaro, Beniamino; Basciu, Alessio; Iaccarino, Alessandra; Droandi, Ginevra; Romano, Giorgio; Citterio, Enrico; Fumero, Andrea; Torracca, Lucia; Pini, Daniela
Abstract: Ventricular assist devices (VADs) are considered the standard of care for end‐stage heart failure (HF) patients. Despite increasing confidence in the technology, evidence data, endorsement by scientific societies and guidelines, the number of implants reached a steady state and is not increasing at the expected pace. This is most likely related to complications that are still burdening the technology and consequently excluding the most needy, ill, and fragile population. In this manuscript we are reporting a single‐center experience in a very fragile, elderly and end‐stage HF population, with a superficial, partial support device: the CircuLite Synergy. The patients were included in the pre‐CE mark clinical study and consequently the device underwent technical adjustment during the support, based on the complications recorded. At our institution were implanted 6 patients overall: 3 patients survived to discharge and 2 survived up to 5 years. Most of the complications recorded were due to patients' frailty and overall clinical conditions. The initial experience with the CircuLite Synergy device is proving that a more "superficial" device might be more tolerable in an elderly, frail population. Partial support has proven hemodynamically efficacious and efficient in relieving heart failure symptoms, improving medical therapy tolerability, and improving quality of life. Unfortunately, the technology was not made available due to financial uncertainty and poor management, but we hope that once the concept has been proved someone will collect the legacy.